An investigation into the relationship between tinnitus distress and cognitive performance - Clarke, N.A. (2021)
Chronic subjective tinnitus (herein referred toas tinnitus) is the conscious perception of sound in the absence of an external sound source. It is very common and a significant proportion of those who experience it find their tinnitus percept distressing. Cognitive task performance has been suggested to be poorer for people with subjective tinnitus, however, research on this topic to date has yielded inconsistent findings. This thesis contributes to understanding of the role of cognitive performance in subjective tinnitus through three studies.